Influência da agua produzida nos parâmetros reológicos de filtração e corrosividade dos fluidos de perfuração aquosos - Oliveira, Ana Karoline de Sousa (Universidade Federal Rural do Semi-Árido, 2018)
Steels are always subject to corrosion, which can be defined as deterioration of the material when subjected to the environment containing oxidizing agents. Pipelines and equipment suffer constant corrosion attacks at all stages of oil and gas production in the oil industry (extraction and refining operations) as well as transportation and storage. The oil industry contains a wide variety of corrosive environments and some of these are unique to this industry. Water produced from petroleum generally has very corrosive characteristics for surface and subsurface equipment due to high salinity. The present work has as objective to evaluate the rheological and corrosive properties of drilling fluids made from the water produced. Statistical planning 2³ was used to evaluate the corrosion rate of the ARBL (High Resistencia Low Alloy), ARAL (High Resistencia High Alloy) and AISI 1020 steels, where the fluid salinity levels were 1%, 3% and 5% %. The results showed that the fluid was a Pseudoplastic and that no large rheological changes were observed, as well as the apparent viscosity and volume of the filtrate, relating them to a response surface for better visualization of the results. The Corrosivity analysis of the steels indicated that the steels suffered a loss of mass during the time they were immersed in the fluid, being ARBL (High Resistencia Lower Alloy) that obtained a higher rate of corrosion, they were presented in the following ascending order of Corrosivity ARAL (High Alloy High Strength), AISI 1020 and ARBL (High Alloy Resistant Steel). The predominance of the corrosive process Uniforme and by Placas was detected
Monografia
Keywords: Corrosão; Aços; Agua Produzida; Fluidos de Perfuração; Corrosion; Steels; Produced Water; Drilling Fluids; ENGENHARIAS::ENGENHARIA MECANICA